Design Learning: Perencanaan Materi Pemuridan dalam Meningkatkan Pengetahuan Alkitab Pemuda - Frendi Sofyan Zebua; Puspita Widia Sari Zebua; Bezeni Waruwu; Martinus Hia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the application of design learning in planning discipleship materials as an effort to improve the Bible knowledge of church youth. This study uses a qualitative approach with an action research method, which is implemented through the stages of planning, action, observation, and reflection. The research subjects were 40 church youth who were actively involved in the discipleship program. Data collection techniques included observation, interviews, questionnaires, and participant reflections before and after the implementation of design learning. The results show that the application of design learning makes a significant contribution to improving the Bible knowledge of youth, which includes cognitive, affective, and psychomotor aspects. Youth not only experienced an increased understanding of the Bible's content, but also showed growth in faith attitudes, spiritual motivation, active participation in learning, and involvement in church services. The design learning approach helps create planned, contextual, and learner-centered discipleship learning. Thus, design learning is proven to be effective and relevant as a youth discipleship strategy in facing the challenges of faith formation in the digital era.